Aplikasi Dosis Pupuk Urea dan Umur Bibit terhadap Pertumbuhan dan Hasil Tanaman Padi Ketan (Oryza sativa glutinous L.) - S Sunawan (Folium : Jurnal Ilmu Pertanian, 2020)
Nowadays glutinous rice productivity is still low even though its production potential is very high. It is caused by the lackness of  special technology for glutinous rice cultivation. Therefore we need cultivation techniques that can increase the production of glutinous rice plants. Application of urea fertilizer in a proper dosage and a proper seedlings age are expected to be able to increase glutinous rice production. This study aimed to get the right dosage of urea fertilizer and the proper age seedlings that can increase glutinous rice production. The study was designed using a Divided Plot Design arranged by  Randomize Block Design, 2 factors (3x3). As Main Plot (PU) was the  dosage  of urea fertilizer (P), consisting of 3 levels: P1 = 100 kg ha-1, P2 = 200 kg ha-1 and P3 = 300 kg ha-1. As the plots  (AP) were the age of seeds (U), consisting of 3 levels: U1 = 14 days, U2 = 21 days, and U3 = 28 days. Variables observed were plant height, number of tillers, number of leaves, leaf area, number of panicles per clump, panicle length, number of grains, number of grained rice, number of empty grains, number of seeds per panicle, fresh weight, dry weight, weight of 1000 grains, and grain weight per hectare. The results showed that the dosage of 300 kg ha-1 Urea (P3) and 14 days seedling ages (U1) showed a good response, so it can be recommended to be applied by the farmers. Keywords: Glutinous rice, urea fertilizer dosage, seedling age